Language Framing Influences Interest in Social-Issue Based Prosocial Behavior - Olagbegi, Olajuwon; Sacco, Donald F.; Brown, Mitch (Studia Psychologica: Theoria et praxis, 2024)
Social activism has become an increasingly ubiquitous route to address perceived inequalities, with racial issues oftentimes being a salient example. Those looking to recruit activists for their cause are oftentimes interested in strategies to elicit participation. Two studies examined how linguistic framings of activism influence interest in such displays. Participants viewed generic low-cost and high-cost prosocial behaviors, described as being in the service of social justice, social activism, or volunteering on a between participants basis. Prosocial interest was highest for behaviors described as serving social justice purposes (Study 1). When the same prosocial behaviors were tied to specific social issues, interest in low-cost prosocial behaviors were higher when they were described as serving social activism (Study 2). Black participants reported more activism interest than White participants in both studies, regardless of framing. Findings could inform best practices for garnering support for various social causes.